Down's syndrome: an atheroma-free model?. Issue 6081 (23rd July 1977) - Murdoch, J C; Rodger, J C; Rao, S S; Fletcher, C D; Dunnigan, M G
Abstract : Postmortem examination of five institutionalised patients with Down's syndrome (DS) aged 40-66 years showed a complete absence of atheroma, while a similar number of mental defectives with DS were found to have mild or severe atheroma. Previous investigation of risk factors for atheroma in 70 patients with DS and 70 age-and sex-matched mental defectives living in the same institution showed significantly lower systolic and diastolic blood pressures in the DS group, with the exception of systolic pressure in men under 40. Fasting serum cholesterol and triglyceride concentrations were similar in the two groups, but triglyceride concentrations were significantly lower than in normal people without a history of vascular disease. These unexplained observations may be relevant in further studies of the pathogenesis of atheroma.